Development of multi-legged robot controller with remotely control system - Ahmad Aqil Safwan, Ahmad Zabidi (2022)
The multi-legged robot is a biologically inspired robot that mimics insect or arthropod creatures. This robot is commonly developed as a mobile robot for a crewless operation that can surpass what a wheeled robot does not. Moreover, this robot can hold both static and dynamic stabilities in its locomotion. In this project, a configurable multilegged robot named Hexapod-to-Quadruped (Hexaquad) robot is focused on improving with stable leg motion and gait pattern. Moreover, the project focuses on developing a new leg shoe for flat terrain on land locomotion. A centralized control unit board is prepared with a 32-bit microcontroller as its processing unit in the control design. The embedded controller design used Simulink code for the real-time and hardware-in-loop method. The project's outcome provides basic motion for each robot's leg including leg reset setting for initial position.